Analysis Of Factors Causing Non-Compliance With Land And Building Tax Payments In Langkat Regency - Sarah Ismail; Nilam Firnanda; Balqis Suci Wahyumia; Renny Maisyarah (Universitas Muhammadiyah Palu, 2026)
The Land and Building Tax (PBB) is one of the key sources of revenue for local governments, including Langkat Regency. However, the realization of PBB-P2 revenue in this region has not been optimal due to the low level of taxpayer compliance. This study aims to analyze the factors influencing non-compliance in PBB payments and to identify the social, economic, and administrative aspects contributing to the low regional tax revenue. This research employs a qualitative approach with data collected through in-depth interviews, observations, and documentation. Data analysis was conducted using the interactive model by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that taxpayer non-compliance is influenced by internal factors such as low awareness and understanding of tax obligations; external factors such as limited socialization, inadequate quality of tax administration services, and insufficient payment facilities; as well as structural factors, including inaccurate tax object data and weak enforcement of sanctions. The most dominant factors are the low awareness of taxpayers and the limited socialization efforts by the local government. These findings highlight the need for strategies to improve tax literacy, enhance administrative services, optimize socialization efforts, and enforce sanctions more consistently to increase PBB payment compliance in Langkat Regency.